Lp-Approximation by Bezier Variant of Certain Summation-Integral Type Operators: Asha Ram Gairola, Girish Dobhal - Team, Support (Thai Journal of Mathematics, 2012)
The problem of Lp−aproximation has been received consideration of many authors. In this paper we establish the direct and inverse theorems for the Bezier variant Mn, of certain summation-integral type operators Mn in Lp−norm using Ditzian-Totik modulus of smoothness. These operators include the well known Baskakov-Durrmeyer and Szasz-Durrmeyer type operators as special cases.